(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: (1) To survey the clinical and paraclinical characteristics of patients with lumbar disc herniation treated at Can Tho Central General Hospital in 2020 - 2023. (2) To evaluate the early results of surgical treatment of lumbar disc herniation by microsurgical discectomy through a balloon tube at Can Tho Central General Hospital in 2020 - 2023. Methods: A retrospective study describing 35 patients diagnosed with lumbar disc herniation through clinical and paraclinical examination and indicated for microsurgical discectomy through a balloon tube at Can Tho Central General Hospital from January 2020 to December 2023. Results: In the study, there were 25 male patients, 10 female patients, with an average age of 44.77 ± 12.74 years. Manual labor occupations accounted for 77.14%. 100% of patients had back pain, radiating along the nerve roots. The type of disc herniation with ruptured fibrous sac and intact nucleus pulposus accounted for 74.29%, with fibrous sac remaining 14.29%, and migration 11.43%. 100% of patients had good wound healing after surgery. Early treatment results assessment according to Macnab at the postoperative time recorded a high rate of 94.29% in the group of patients with very good and good levels. Conclusion: Microsurgical discectomy through a dilator tube is a safe method with a low complication rate.